The ecology of a keystone seed disperser, the ant Rhytidoponera violacea - Lubertazzi, D.; Aliberti Lubertazzi, M.; McCoy, N.; Gove, Aaron; Majer, Jonathan; Dunn, Robert (University of Wisconsin, 2010)
Rhytidoponera violacea (Forel) (Hymenoptera: Formicidae) is a keystone seed disperser in Kwongan heathland habitats of southwestern Australia. Like many myrmecochorous ants, little is known about the basic biology of this species. In this study various aspects of the biology of R. violacea were examined and the researchers evaluated how these characteristics may influence seed dispersal. R. violacea nesting habits (relatively shallow nests), foraging behavior (scramble competitor and lax food selection criteria), and other life history characteristics complement their role as a mutualist that interacts with the seeds of many plant species.